Volta Photo starring Sanlé Sory and the people of Bobo-Dioulasso in the small but musically mighty country of Burkina Faso - Witkovsky, Matthew S. 1967-; Byrd, Antawan I.; Mazzoleni, Florent 1974- (Steidl, 2018)
The studio photographs of Sory Sanlé and his participation in the vibrant music scene in Bobo-Dioulasso give us a picture of a cosmopolitan city shaping its independent identity in the 1960s through to the 80s, the heyday of West African independence movements. Vintage photographs, seven-inch record sleeves and studio accessories are all reproduced in the most extensive portrayal to date of photography and music as key popular art forms with local, national and international resonance
Published on the occasion of an exhibition held at the Art Institute of Chicago, April 27, 2018-August 29, 2018
Keywords: Sory Sanlé -- 1943-; Porträtfotografie; Burkina Faso; Sory Sanlé / 1943- / Exhibitions; Sory Sanlé / 1943- / Interviews; Portrait photography / Burkina Faso / Exhibitions; Africans / Pictorial works / Exhibitions; Popular music / Burkina Faso / Exhibitions; PHOTOGRAPHY / Photoessays & Documentaries; Africans; Popular music; Portrait photography; Exhibition catalogs; Exhibition, pictorial works; Interviews; Ausstellungskatalog -- Art Institute of Chicago -- 27.04.2018-19.08.2018 -- Chicago, Ill.; Bildband